When the Old Will No Longer Do: School and Community Practices for Student Homelessness Amid COVID-19. (December 2021) - Pavlakis, Alexandra E.; Roberts, J. Kessa; Richards, Meredith P.
In this qualitative case study, we employ 29 semistructured interviews and an array of supplemental data to explore why and how COVID-19 shaped school and community practices around student and family homelessness in Houston, Texas. Drawing on Small's notion of organizational embeddedness, we find that COVID-19 fundamentally altered school and community practices, as educators and providers faced resource constraints, new concerns about safety, and evolving student and family needs. Providers struggled to meet the depth of need stemming from COVID-19; however, they also embraced innovation in adapting their practices to the pandemic era. We find that this adaptation occurred along a continuum, ranging from pausing or stopping existing practices to developing new practices from scratch. We conclude with implications for theory, research, policy, and practice.